Hong Kong Kindergarten Teachers' Satisfaction and Engagement in a Music-and-Movement Online Professional Development Course - Siu-Ping Ng; Alfredo Bautista (MDPI AG, 2024)
Online professional development (PD) can be a sustainable and easily scalable alternative to provide early childhood teachers with training opportunities. However, there is limited research on teachers' levels of satisfaction and engagement in online PD initiatives. Understanding teachers' levels of satisfaction and engagement is crucial, as these may influence the effectiveness of online PD in benefiting teachers and ultimately young children. This study aimed to examine Hong Kong kindergarten teachers' satisfaction and engagement in a music-and-movement (M&M) online PD course. This study involved 56 participants who received an 11-week online PD course. Questionnaires were administered after course completion. Data were analyzed using descriptive statistics and t-tests. Participants had high levels of satisfaction with the course, particularly those with no or some M&M background, who were more satisfied with the course content and instruction. Participants had moderate-to-high levels of engagement in the course, particularly those with no or some M&M background, who were more emotionally engaged. We conclude that sustainable and easily scalable online PD initiatives can result in high levels of satisfaction and engagement among kindergarten teachers, especially those with limited M&M background. This study supports the idea that online PD can be responsive to teachers' needs and preferences.